PENGEMBANGAN APLIKASI AUGMENTED REALITY BOOK PENGENALAN OBJEK WISATA TAMAN UJUNG SOEKASADA DAN TAMAN AR TIRTA GANGGA DI KABUPATEN KARANGASEM - Putu Angga Sudyatmika; Padma Nyoman Crisnapati; I Gede Mahendra Darmawiguna; Made Windu Antara Kesiman (Universitas Pendidikan Ganesha, 2014)
Taman Ujung Soekasada and Tirta Gangga is a famous tourist attraction inKarangasem regency. Taman Ujung is located at the village of Tumbu, district of Karangasem. The park was built in 1919 by the king of Karangasem, namely I Gusti BagusJelantik with the purpose to entertain important guests who visitied the region of Karangasem.Tirta Gangga was rebuilt in 1948 on the initiative of The King of Karangasem namely AnakAgung Anglurah Ketut Karangasem. Situated in Ababi Village, 6 kilometers northern Taman Ujung Soekasada. This water park built as a place for bathing the King and his family.This research is aims to develop an android-based application that can be used as a medium for learning and preserving Taman Ujung Soekasada and Tirta Gangga. The researchmethod used was research and development by using the model of the waterfall. Thisapplication uses the vuforia library to display 3 dimensional building objects into a real environment by using the book and the android smartphone.The end of result is a book that contains about information and images related toTaman Ujung Soekasada and Tirta Gangga that functioned as a marker as well as android based on Augmented Rality application that is capable of displaying the object of Taman Ujung and Tirta Gangga buildings in 3 dimensional above the marker complete with thenarrative sound explanation